A Global Perspective on Screening. Issue 4 (23rd July 2020) - Pollack, Erica B; Mollura, Daniel R; Chong, Alice; Harvey, Susan C; Scheel, John R
Abstract: Breast cancer is emerging as a major global public health problem. Incidence and mortality continues to rise in low- and middle-income countries (LMICs). A significant and growing disparity exists between high-income countries and LMICs in the availability of screening services and associated preventable mortality. However, population imaging-based screening programs are not appropriate for all settings. Planners should perform a thorough assessment of the target setting prior to implementing any breast cancer detection program, as appropriate guidelines vary according to the resources available. Financial, social, and cultural barriers to breast cancer care need to be addressed to sustainably improve the morbidity and mortality of the populations and make efficient use of available services. Creative approaches, such as mobile and portable imaging and bundling of services, can facilitate the installation of early breast cancer detection programs in LMICs. While image-based screening programs are not initially resource-appropriate in many LMICs, planners can work towards this goal as part of their comprehensive breast cancer detection strategy.